BEX1 Is Differentially Expressed in Aldosterone-Producing Adenomas and Protects Human Adrenocortical Cells From Ferroptosis. Issue 5 (22nd March 2021) - Yang, Yuhong; Tetti, Martina; Vohra, Twinkle; Adolf, Christian; Seissler, Jochen; Hristov, Michael; Belavgeni, Alexia; Bidlingmaier, Martin; Linkermann, Andreas; Mulatero, Paolo; Beuschlein, Felix; Reincke, Martin; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Aldosterone-producing adenomas (APAs) are a major cause of primary aldosteronism. Somatic mutations in ion channels and transporters drive the aldosterone overproduction in the majority of APAs with mutations in the KCNJ5 G protein-coupled potassium channel predominating in most reported populations. Our objective was to gain insight into biological mechanisms of APA tumorigenesis by comparing transcriptomes of APAs of distinct sizes by mRNA sequencing analysis (9 APAs with adenoma diameter ≥30 mm versus 12 APAs ≤10 mm). Genes with significantly altered expression levels between these 2 groups were identified in APAs with no mutation detected (348 genes) and with a KCNJ5 mutation (155 genes). We validated the differential expression of 10 genes with a known function related to cell death and proliferation in an expanded sample set of 71 APAs by real-time quantitative polymerase chain reaction (58 macro-APAs, diameter ≥10 mm; 13 micro-APAs, diameter <10 mm). We focused on BEX1 that was upregulated in micro-APAs relative to macro-APAs (2.76-fold, P <0.001) and compared with paired adrenal cortex (3.85-fold, P <0.05), and showed a linear negative correlation with APA diameter in the no mutation detected group (r=−0.501, P =0.007). Compared with control cells, stable expression of BEX1 in human adrenocortical cells did not alter cell cycle progression or sensitivity to apoptosis but conferred protection from ferroptosis ( P <0.01), a form of regulated cell death, measured by flow cytometry. Taken together, these findings demonstrate that BEX1 promotes cell survival in adrenal cells by mediating the inhibition of ferroptosis and suggest a function for BEX1 in the pathogenesis of APAs.